2020
DOI: 10.1371/journal.pone.0231308
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper arm circumference as a simple tool for identifying central obesity and insulin resistance in type 2 diabetes

Abstract: Background Our research aimed to explore the correlation between mid-upper arm circumference (MUAC) and central obesity and insulin resistance (IR) in Chinese subjects with type 2 diabetes. Materials A total of 103 participants (60 men) were recruited in our study. MUAC was measured around the mid-arm between the shoulder and elbow. Waist circumference (WC) was obtained as central obesity parameter, and the IR parameter of Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) was calculated. The subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 46 publications
4
26
2
4
Order By: Relevance
“…Our findings are in line with existing literature on the association between leg adiposity and various cardiometabolic conditions [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. While prior studies have generally not focused on BP or hypertension as a primary outcome, they have consistently reported inverse associations between leg adiposity measures and metabolic risk factors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are in line with existing literature on the association between leg adiposity and various cardiometabolic conditions [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. While prior studies have generally not focused on BP or hypertension as a primary outcome, they have consistently reported inverse associations between leg adiposity measures and metabolic risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, Han et al [ 25 ], using the Korean NHANES, showed that leg/total% displayed the strongest association with atherosclerotic cardiovascular disease risk. Interestingly, studies that additionally assessed arm adiposity have found no significant association, and in some cases positive associations, with metabolic risk factors [ 17 , 20 , 32 , 33 ]. Our findings also corroborate a positive association between arm/total% and SBP and hypertension that was later attenuated by adjustment for cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the estimate formula using BMI and UC has the highest values of R 2 , which is an index used to evaluate the suitability of multiple regression analysis. It has been reported that the mid upper arm circumference is associated with WC as central obesity [23] . Therefore, the estimate formula using BMI and UC may have the highest values of suitability from the multiple regression analysis in this study.…”
Section: Limb Circumferencementioning
confidence: 98%
“…[76] obwód środkowy ramienia jest dodatnio skorelowany z asymetryczną dimetyloargininą wiązaną z chorobami układu sercowo-naczyniowego [77]. Jest skutecznym narzędziem do oceny otyłości centralnej [78] oraz insulinooporności u pacjentów z cukrzycą typu 2 [79]. Wskaźnik ten jest wiązany z występowaniem wyższego stężenia kwasu moczowego oraz cholesterolu o niskiej gęstości i niższymi wartościami lipoprotein o wysokiej gęstości [79].…”
Section: Obwód śRodkowy Ramienia -Muac (Mid-upper Arm Circumference)unclassified